O Programa Bolsa Família: uma análise do impacto sobre o nível de pobreza no Brasil (de 2012 a 2022) - Débora da Silva Antonio; Ana Cristina Lima Couto (Revista de Economia Mackenzie)
Poverty is a persistent problem in Brazil, and, as the Bolsa Família Program (PBF) is one of the main income transfer policies that aims to alleviate poverty in the country, this study analyzes the impact of the PBF on poverty in Brazil in the period from 2012 to 2022 through the panel data model for the twenty-seven Federation Units. It was found that transfers from income transfer programs have a modest impact on poverty reduction, while the reduction of inequality and economic growth exert a more substantial influence on it, and it is possible to conclude that policies focused on reducing inequality and increasing income ha-ve a more effective contribution to reducing poverty than income transfer policies such as the PBF.